Evaluation method of snow accretion around train bogie using model vehicle running apparatus - Hajime TAKAMI; Yuto ARAKI (Nihon Kikai Gakkai ronbunshu, 2024)
A method for evaluating snow accretion around a train bogie was investigated using a newly developed model vehicle running apparatus. The model train running apparatus is capable of running a 1/11 scale model train on a 384 m track at a maximum speed of 120 km/h. The phenomenon of snow accretion due to train running was experimentally simulated by setting up a simulated snow condition in which simulated snow particles were deposited on the track. Comparison of snow accretion on the end blocking vertical panel downstream of the bogies of an intermediate car between real cars and model running tests confirmed that the general characteristics of the snow distribution adhered on the panel can be reproduced. As a result of investigating the growth process of the snow accretion from the model experiment using image processing and 3D scanning, it is found that the initial snow accretion starts from the under side of the vertical panel downstream of the bogie, especially near the wheels. As the travel distance of the snowed section increased, the snow accretion on the under side of the vertical panel extended over the bogie cavity, and snow accretion also occurred on the top and sides of the vertical panel. Eventually, the entire vertical panel was found to be covered with snow accretion.